2007
DOI: 10.1074/jbc.m610447200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor 1/Insulin Signaling Activates Androgen Signaling through Direct Interactions of Foxo1 with Androgen Receptor

Abstract: The androgen-androgen receptor (AR) system plays vital roles in a wide array of biological processes, including prostate cancer development and progression. Several growth factors, such as insulin-like growth factor 1 (IGF1), can induce AR activation, whereas insulin resistance and hyperinsulinemia are correlated with an elevated incidence of prostate cancer. Here we report that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 39 publications
11
143
0
2
Order By: Relevance
“…Li et al observed that inhibition of PI3-kinase was able to inhibit the transcriptional activity of AR resulting in decreased androgen-induced proliferation (Li et al, 2001). FOXO1 was found to directly associate with the androgen receptor, and thereby inhibit its transcriptional activity (Li et al, 2003;Fan et al, 2007). Utilizing transcription reporter assays it was shown that AR, in a ligand-dependent manner, could also reciprocally inhibit both FOXO1 and FOXO3 activity.…”
Section: Foxo Partners Regulating Muscle Homeostasismentioning
confidence: 99%
“…Li et al observed that inhibition of PI3-kinase was able to inhibit the transcriptional activity of AR resulting in decreased androgen-induced proliferation (Li et al, 2001). FOXO1 was found to directly associate with the androgen receptor, and thereby inhibit its transcriptional activity (Li et al, 2003;Fan et al, 2007). Utilizing transcription reporter assays it was shown that AR, in a ligand-dependent manner, could also reciprocally inhibit both FOXO1 and FOXO3 activity.…”
Section: Foxo Partners Regulating Muscle Homeostasismentioning
confidence: 99%
“…[175][176][177] IGF-1 stimulates 5α-reductase, adrenal and gonadal androgen synthesis, AR signal transduction, sebocyte proliferation and lipogenesis. [178][179][180][181][182][183][184] Milk consumption results in a significant increase in IGF-1 serum level and exerts strong insulinotropic effects comparable to high glycaemic food. 185,186 Insulin induces hepatic IGF-1 secretion, and both hormones amplify the stimulatory effect of GH on sebocytes and augment mitogenic downstream signaling pathways of insulin receptors, IGF-1 receptor and FGFR2b (Fig.…”
Section: Interleukin-1α Network In Keratinocytesmentioning
confidence: 99%
“…(55) A recent study showed that PI3K/Akt pathway inhibited the activity of Foxo1, which is a corepressor for AR, providing another mechanism of AR activation through this pathway. (56) In the context of the PI3K/Akt pathway, it is important to mention the phosphatase and tensin homolog deleted on chromosome ten (PTEN), also known as mutated in multiple advanced cancers (MMAC1), which is a negative regulator of the PI3K/Akt pathway. (57) FISH analyses have indicated that about 70% of primary prostate cancer samples and about 20% of the high grade PIN (prostatic intraepithelial neoplasia) samples have genomic deletions of PTEN.…”
Section: Tmprss2mentioning
confidence: 99%